2020
DOI: 10.14742/ajet.5477
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating student engagement through educational technology in higher education: A systematic review in the field of arts and humanities

Abstract: Understanding how educational technology can enhance student engagement is becoming increasingly necessary in higher education, and particularly so in arts and humanities, given the communicative nature of courses. This narrative systematic review synthesises 42 peer-reviewed arts and humanities articles published between 2007-2016, indexed in four international databases. The results indicate that the majority of research has been undertaken in language learning, predominantly in East Asian countries, with li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(89 citation statements)
references
References 63 publications
(93 reference statements)
1
58
0
6
Order By: Relevance
“…In contrast to the positive discourse related to blended learning (Castro 2019;Garrison and Kanuka 2004), some studies reported students feeling pressured or overwhelmed by blended learning and preferring a face-to-face environment for learning (Bedenlier et al 2020). Other studies uncovered related challenges, for both PSTs and teachers, with the use of technology, usually related to the inability to make the most of available technology (Rasheed, Kamsin, and Abdullah 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the positive discourse related to blended learning (Castro 2019;Garrison and Kanuka 2004), some studies reported students feeling pressured or overwhelmed by blended learning and preferring a face-to-face environment for learning (Bedenlier et al 2020). Other studies uncovered related challenges, for both PSTs and teachers, with the use of technology, usually related to the inability to make the most of available technology (Rasheed, Kamsin, and Abdullah 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the results presented here provide an initial window into the overall body of research identified during the search, and further research is being undertaken to provide deeper insight into discipline specific use of technology and resulting student engagement using subsets of this sample (Bedenlier, 2020a; Facilitating student engagement through educational technology: A systematic review in the field of education, forthcoming).…”
Section: Limitationsmentioning
confidence: 99%
“…The Heutagogy approach proposed for TPE The Heutagogy approach designed in this study encourages participants to engage in learning via Google Classroom, allowing participants to review and provide comments and suggestions on colleagues using a reflective worksheet. A study by Bedenlier et al (2020) found that online media that provide a space for discussion can stimulate learners by alleviating anxiety in participants to create responses and encourage participants to contribute to the learning. Kahu and Nelson (2018) emphasise that engaging student in learning is the key factor in achieving successful learning.…”
Section: Post-testmentioning
confidence: 99%
“…Kahu and Nelson (2018) emphasise that engaging student in learning is the key factor in achieving successful learning. One way to enhance learners engagement is by applying educational technology such as online learning tools (Bedenlier et al, 2020). Educational technology facilitates learners with intensive learning that stimulates participants to actively participate in learning (Bond et al, 2020).…”
Section: Post-testmentioning
confidence: 99%
See 1 more Smart Citation